Redução de danos e vínculos com usuários de drogas: a escuta do olhar de um palhaço - Azevedo, Rafael Torres (2017)
The dissertation to be defended in the Post Graduation Program in Psychology of the Federal University of Uberlândia aims to show the researcher’s experiences implicated in the research process, who proposed to work as a clown with a team of consultation office in the street in a medium-sized city of the “Triângulo Mineiro”, and in this way map the therapeutic effects that this behavior and this way to approach the street population (most of them users of alcohol and other drugs) can have in creating bonds. The methodology used was the mapping that worked as a way to follow the meetings as they were happening and being lived among researcher and participants. In these traces made of meetings and disagreements, always considering the implication of the researcher in this process, it was evidenced the value of respect and affection in approaching and closeness with the users and the territory. It is also important to think about drugs in the country considering the knowledges, practices and achievements of the anti-asylum fight, in a context of conflict between an instituted drug war and treatment for total abstinence, and its counterpoint; harm reduction and defense of drug use regulations that can be able to broaden clinic’s therapeutic possibilities to take care of those who have problems with the use and want treatment, besides respecting the choices made by those who want to use alcohol and other drugs, according to their wish and convenience.